Kinetics of paper drying and thermodynamic driving forces - Valent Vladimir; Krgović Milorad; Nikolić Srećko (Hemijska Industrija, 2007)
Kinetics of paper drying, its relation with thermodynamic drying agent parameters and dynamics of technological process participants was analyzed. The importance of thermodynamic states of drying agents, rate of the participants versus heat transfer and wet transfer coefficients to drying agents were discussed.